1999
DOI: 10.1002/(sici)1520-6807(199911)36:6<515::aid-pits7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of information on perceptions of stimulant medication efficacy for treatment of attention-deficit hyperactivity disorder

Abstract: A study on the perceptions of stimulant medications prescribed for children with attention‐deficit hyperactivity disorder (AD/HD) was conducted. Students, enrolled in introductory level psychology courses at a midwestern university participated voluntarily in the study (N= 36). After viewing a video that simulated the feelings a child with AD/HD experiences, participants were randomly assigned to two treatment groups. The popular information group read an article on AD/HD similar to that which is most often pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Few other studies have explored this issue, but it is likely that the lack of positive effects could be just as important as the presence of negative effects. It has also been suggested that the type of information a person receives about stimulant medication influences that person's perception of medication efficacy (Borgschatz, Frankenberger, & Eder, 1999). When studying medication treatment in children, parental perceptions of stimulant treatment in general should be of interest, as children are likely to be influenced by what their parents think about the treatment.…”
Section: Previous Studies Using Self-reportsmentioning
confidence: 99%
“…Few other studies have explored this issue, but it is likely that the lack of positive effects could be just as important as the presence of negative effects. It has also been suggested that the type of information a person receives about stimulant medication influences that person's perception of medication efficacy (Borgschatz, Frankenberger, & Eder, 1999). When studying medication treatment in children, parental perceptions of stimulant treatment in general should be of interest, as children are likely to be influenced by what their parents think about the treatment.…”
Section: Previous Studies Using Self-reportsmentioning
confidence: 99%
“…years, the use of stimulant medication has greatly increased as the main treatment for ADHD (Borgschatz et al 1999;MTA Cooperative Group 2004).…”
mentioning
confidence: 99%
“…Parents with higher knowledge (accurate and comprehensive information about ADHD and its treatment) of ADHD had more positive opinions of non-pharmacological interventions, but not pharmacological interventions than did parents with less knowledge (less accurate and complete information on ADHD and its treatment). Although parents reported they favored non-pharmacological interventions, the literature shows pharmacological interventions increasing in usage for the treatment of ADHD (Borgschatz et al 1999; Moline and Frankenberger 2001;Snider et al 2000). It is unclear why parents have typically endorsed non-pharmacological treatments, while actually utilizing pharmacological treatments for ADHD.…”
mentioning
confidence: 99%